Examining Teacher Characteristics, School Conditions, and Attrition Rates at the Intersection of School Choice and Rural Education. Issue 2 (3rd April 2021) - Crouch, Michael; Nguyen, Tuan D.
ABSTRACT: While prior research has examined teachers in rural schools and teachers in charter schools, there has been little research into the intersection of rural and charter schools. Using nationally representative data, we examine the extent to which teacher characteristics, school characteristics, and teacher mobility vary based on the urbanicity of schools and whether the school is a public or charter school. We find that teachers in rural charter schools turn over at a significantly lower rate than teachers in urban charter schools and are significantly more likely to be young, novice teachers than their rural public school counterparts. We provide evidence that, in comparison with rural settings, it is important to consider urban and suburban context separately, particularly with respect to charter schools as urban charter teacher demographics and the schools in which they teach are substantially different than those of suburban charter teachers. Our work suggests research cannot ignore how teacher demographics, teacher qualifications, and the students they teach vary significantly given the context of the intersection of school choice and rural education.